El cultivo de la yuca en Republica Dominicana - Sosa V., M. (International Center for Tropical Agriculture, 1991)
Different aspects of cassava cultivation in the Dominican Republic are described, namely edaphoclimatic regions, production, trade, consumption, production systems, var., and uses. Production constraints include inadequate land preparation, limited use of recommended agronomic practices, diseases and pests, var. mixtures, and limited use of var. adapted to regional conditions, deficient weed control, low application of fertilization, inadequate association of cassava in multiple cropping systems, and early harvest. Both the Centro Sur de Desarrollo Agropecuario and the Centro Norte de Desarrollo Agropecuario have cassava plant breeding programs; main activities are maintenance of international and national collections; morphological classification of var., development of lines through polycrosses and directed crosses, introduction of lines in the form of sexual seed or meristem tissues, and assessment of var. and lines regarding yield and response to negative facotrs. Background information is given on both research programs and their current status is analyzed. A basic structure exists to receive from CIAT germplasm in the form of meristem tissue cultures. Future plans include increased cassava cultivation for a total of 21,699 ha; increased production destined to animal nutrition and starch production; and strengthening of the services distributing planting material, mechanization, and agricultural extension. (CIAT)